Total service quality management and the service industry: Evidence from international airlines - Usman, Umar (2013)
Today the airline industry is one of the fastest and largest growing industries in the world because of its importance in facilitating national and international relation among st countries, Tangibles, Reliability, Competence, Responsiveness, and Empathy are the core characteristics of service industry.In line with the international standard parameters the study which to recommend to the airline industry to enhance the level of customer satisfaction, customer royalty and customer retention in the industry by providing safety of their life and property, restore full confidence on their quality of service delivery and delight their existing customers in order to attract potential customers.